Experimental investigations on the compaction energy for a robotic rammed earth process - Schmitz, Linus Paul; Gosslar, Joschua; Dorresteijn, Evelien; Lowke, Dirk; Kloft, Harald (Frontiers in Built Environment, 2024)
Rammed earth is a construction material with a long history of traditional manufacturing. Due to its low environmental impact, positive impact on indoor climate and completely recyclable nature, its demand is also increasing in modern construction industry. However, as a consequence of the predominantly manual manufacturing processes, the production of rammed earth components is both inefficient and costly. Through the implementation of automated and robot-aided fabrication processes in the field of rammed earth construction, the opportunity to advance the digitalization of the field can raise to a new level. In this paper, general studies on the interrelation of process and material parameters and their influence on the compaction results were conducted as a basis for the development of a prototypic robotic manufacturing process. The results show that reducing the layer height can significantly decrease the impact energy. Additionally, it was shown that there is a minimum number of strokes and a minimum ramming frequency required for sufficient compaction. Furthermore, a possible workflow for a specific control of the required dry density through variation of the compaction energy with regard to the present moisture content was identified.